About improving the system of personnel training for construction industry (Международный научный журнал «Инженер», 2026)
The ways of improvement of personnel training for construction industry of the Republic of Uzbekistan in modern conditions are considered. The existing problem of the branch, connected with acute shortage of highly qualified engineering personnel is outlined. The problem of admission to the profession is posed.